Kajian Penggunaan Biji Saga Merah (Adenanthera pavonina L.) Terhadap Sifat Kimia dan Organoleptik Sambal Pecel - Octavia Diva Syafira; Yossi Wibisono (JOFE : Journal of Food Engineering, 2023)
Pecel sauce is served as a complementary seasoning, to adding additional flavor. Pecel sauce is made by mixing ground peanuts, palm sugar, garlic, chilies, lime leaves, aromatic ginger. In this study, peanuts were substituted and replaced with red saga seeds, so the pecel sauce was not prone to rancidity. The purpose of this study was to determine the effect of red saga seeds on fat content, protein content, and organoleptic of pecel chili. The use of red saga seeds is as much as 0% (Fa), 25% (Fb), 50% (Fc), 75% (Fd), and 100% (Fe). The results of this study are the increasing use of red saga seeds, the lower the fat content, the higher the protein content, and the lower the preference level.